Cardiac resynchronization therapy response in cardiac sarcoidosis. (4th August 2022) - Shabtaie, Samuel A.; Sehrawat, Ojasav; Lee, Justin Z.; Cha, Yong‐Mei; Mulpuru, Siva K.; Kowlgi, Narayan G.; Siontis, Konstantinos C.; Rosenbaum, Andrew N.; Bois, John P.; AbouEzzeddine, Omar F.; Noseworthy, Peter A.; Asirvatham, Samuel J.; et al.
Abstract: Introduction: Cardiac sarcoidosis (CS) is a nonischemic cardiomyopathy (NICM) characterized by infiltration of noncaseating granulomas involving the heart with highly variable clinical manifestations that can include conduction abnormalities and systolic heart failure. Cardiac resynchronization therapy (CRT) has shown significant promise in NICM, though little is known about its efficacy in patients with CS. Objective: To determine if CRT improved cardiac remodeling in patients with CS. Methods: We retrospectively reviewed all patients with a clinical or histological diagnosis of CS who underwent CRT implantation at the Mayo Clinic enterprise from 2000 to 2021. Baseline characteristics, imaging parameters, heart failure hospitalizations and need for advanced therapies, and major adverse cardiac events (MACE) were assessed. Results: Our cohort was comprised of 55 patients with 61.8% male and a mean age of 58.7 ± 10.9 years. Eighteen (32.7%) patients had definite CS, 21 (38.2%) had probable CS, while 16 (29.1%) had presumed CS, and 26 (47.3%) with extracardiac sarcoidosis. The majority underwent CRT‐D implantation ( n  = 52, 94.5%) and 3 (5.5%) underwent CRT‐P implantation with 67.3% of implanted devices being upgrades from prior pacemakers or implantable cardioverter defibrillators. At 6 months postimplantation there was no significant improvement in ejection fraction (34.8 ± 10.9% vs. 37.7 ± 14.2%, p  = .331) or left ventricular end‐diastolic diameter (58.5 ± 10.2 vs. 57.5 ± 8.1 mm, p  = .236), though mild improvement in left ventricular end systolic diameter (49.1 ± 9.9 vs. 45.7± 9.9 mm, p  < .0001). Within the first 6 months postimplantation, 5 (9.1%) patients sustained a heart failure hospitalization. At a mean follow‐up of 4.1± 3.7 years, 14 (25.5%) patients experienced a heart failure hospitalization, 11 (20.0%) underwent cardiac transplantation, 1 (1.8%) underwent left ventricular assist device implantation and 7 (12.7%) patients died. Conclusions: Our findings suggest variable response to CRT in patients with CS with no overall improvement in ventricular function within 6 months and a substantial proportion of patients progressing to advanced heart failure therapies. Abstract : Summary of the response to cardiac resynchronization therapy (CRT) in patients with cardiac sarcoidosis (CS). There was a variable response to CRT in patients with CS with no overall improvement in ventricular function within 6 months.